Original paperThe relation between type D personality and the clinical condition of patients suffering from psoriasis - Basińska, Małgorzata A.; Woźniewicz, Agnieszka (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
Introduction: Type D personality is the last distinguished specific type of personality that is characterised by two dimensions: a tendency for feeling negative emotions – depression, anxiety, anger or hostility, and a tendency for withdrawal from the society. The latest research shows the significant role played by type D personality in the aetiology and course of a variety of diseases. Aim: The article discusses the problem of the occurrence of type D personality in the group of patients suffering from psoriasis. Diversities in the clinical condition of psoriasis patients due to increasing type D personality traits are specified. Material and methods: Ninety psoriasis patients and 86 healthy subjects participated in the research. In the research questionnaires, the scale for assessing increasing psoriasis complaints and the DS-14 scale to assess type D personality were applied. Results: Research results made it possible to corroborate more frequent occurrence of type D personality among psoriasis patients. Moreover, it was found that with increasing negative affectivity – one of type D personality components – complaints increase as far as the clinical condition of psoriasis patients is concerned. Conclusions : Monitoring of psychological well-being of psoriasis patients, especially within type D personality, seems to be a vital element, irrespective of purely medical treatment.